Officiating speech teaching collaboration day between The Faculty of Hotel and Tourism Management, UiTM Puncak Alam and Universitas Asa Indonesia (ASAINDO), and the signing ceremony of a Memorandum of Understanding (MOU) / Prof. Dr Mohd Hafiz Mohd Hanafiah - Mohd Hanafiah, Mohd Hafiz (2025)
Welcome all of you to the Teaching Collaboration Day, co-hosted by the Faculty of Hotel and Tourism Management, UiTM Puncak Alam and Universitas ASA Indonesia (ASAINDO).